Respuesta :

Answer:

  (x, y, z) = (3, -1, -3)

Step-by-step explanation:

The attached graph shows a solution that involves solving the system of equations that results from substituting for z. The second equation is used to write an expression for z that is substituted into the first and third equations.

One of the things we observe in this solution is that substituting into the first equation effectively eliminates x and z, so we learn immediately that y=-1.

That is, subtracting the second equation from the first gives ...

  (2x +8y +z) -(2x +y +z) = (-5) -(2)

  7y = -7

  y = -1

__

The solution by graphing is (x, y, z) = (3, -1, -3).

Ver imagen sqdancefan